The Transformation of Property Rights - Trazegnies Granda, Fernando de (1978)
In the present article the evolution of property is exposed. Previously, the essence of property was constituted by the right of enjoyment, disposition and organization of social work. Now, the property covers various aspects such as the relationship between the shareholder and its action, the right of the owner of rental houses, the relationship between the company and its asset assets. For all these reasons, the author affirms that property has become an analogical concept that allows confronting diverse realities. First of all, the concept of Napoleonic property will be taken as the starting point of reference, to then compare and observe the changes made in the legal system. Then analyze what is the role of property as an instrument and manifestation in society. In other words, the functioning of the liberal society within which classical property is developed will be examined to determine the role that has been assigned to property within that context. In this line, the classic property has been divided into a "moral" right and a "patrimonial" right, and the attributes of the property are divided between both types of rights. Secondly, parallel to the "transformation of the thing" there has been a "subject revolution" of property. This is because the twentieth century we observed that the ownership of the means of production has completely distanced itself from the individual; belongs now to companies. Consequently, man has been split in his activity: on one side is his productive activity, which is organized through socialized forms such as the corporation, the state company or other variants; On the other hand, there is his private life, with his immediate consumption goods. In short, it could be said that the main characteristic of the transformations that has occurred in the ideas of property in recent times is that the logical unity of the traditional term has been broken.